Effect of Joints’ Configuration Change on the Effective Mass of the Robot - Abdel-Nasser Sharkawy (Association for Scientific Computing Electronics and Engineering (ASCEE), 2022)
Effective mass of robot is considered of great significance in enhancing the safety of human-robot collaboration. In this paper, the effective mass of the robot is investigated using different joint configurations. This investigation is executed in two steps. In the first step, the position of each joint of the robot is changing alone, whereas the positions of the other joints of the robot are fixed and then the effective mass is determined. In the second step, the positions of all joints of the robot are changing together, and the effective mass of the robot is determined. From this process, the relation between the effective mass of the robot and the joint configurations can be presented. This analysis is implemented in MATLAB and using two collaborative robots; the first one is UR10e robot which is a 6-DOF robot and the second one is KUKA LBR iiwa 7 R800 robot which is a 7-DOF robot. The results from this simulation prove that the change in any joint position of the robot except the first and the last joint affect the effective mass of the robot. In addition, the change in all joints’ positions of the robot affect the effective mass. Effective mass can thus be considered as one of the criteria in optimizing the robot kinematics and configuration.